Traditions of S.T. Coleridge’s ‘The Rime of the Ancient Mariner’ in ‘The Ballad of Reading Gaol’ by O. Wilde - Dmitry Nikolayevich Zhatkin; Anna A. Ryabova (Space and Culture, India, 2019)
This article aims to analyse the poetic traditions of The Rime of the Ancient Mariner by S.T. Coleridge, which migrated into The Ballad of Reading Gaol by O. Wilde. A comparative analysis of original poems and their Russian translations reveals a thematic and structural link that connects these two poems. The article highlights the common features and the differences in literary devices used by Coleridge and Wilde to transmit the complex concepts of suffering and forgiveness through their characters and to declare values and philosophical ideas. The literary devices in point define how these concepts are covered, and serve a common theme in the work of Coleridge and Wilde. The article also provides arguments to confirm the social situation described in the works.